Pengaruh Pembelajaran Responsi Pada Mata Kuliah Kalkulus II Terhadap Hasil Belajar Mahasiswa Program Studi Pendidikan Matematika FIP UPH - Desri Kristina Silalahi; Dylmoon Hidayat; Jacob Stevy Seleky; Oce Datu Appulembang; Robert Harry Soesanto (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Kristen Indonesia, 2019)
The achievement of the graduates profile which is the goal of Mathematics Education majors Teachers College UPH is to prepare teacher candidates who have the character, calling, and competence also the graduates can role as a Mathematics teacher know the concept of knowledge. However, in the achievement of the graduates profile has not been satisfactory, because results of learning are low in some mathematics courses, especially in Calculus II course. Based on the problem, major Teachers College do a structured academic activity that is response learning. The research method used is control group posttest only design. The sample of the research are the students of Mathematics Education major that take the Calculus II course in the academic year 2015/2016 as the control group and who take the Calculus II course in the academic year 2016/2017 as the experimental group. The improvement of this reponse learning result is seen from t-test analysis, obtained the decision of hypothesis test is exist significant difference between the control class and the experimental class. Keywords : response, calculus II, learning result